Accelerating open science: The collaborative replications and education project (CREP) - Pfuhl, Gerit; Grahe, Jon (Septentrio Conference Series, 2018)
Watch the VIDEO. Recent years have seen a revolution in publishing, and large support for open access publishing. There has been a slower acceptance and transition to other open science principles such as open data, open materials, and preregistration. To accelerate the transition and make open science the new standard, the collaborative replications and education project (CREP; http://osf.io/wfc6u/)) was launched in 2013, hosted on the Open Science Framework (osf.io). OSF is like a preprint, collecting partial data with each individual contributors project. CREP introduces open science at the start of academic research, facilitating student research training in open science and solidifying behavioral science results. The CREP team attempts to achieve this by inviting contributors to replicate one of several replication studies selected for scientific impact and suitability for undergraduates to complete during one academic term. Contributors follow clear protocols with students interacting with a CREP team that reviews the materials and video of the procedure to ensure quality data collection while students are learning science practices and methods. By combining multiple replications from undergraduates across the globe, the findings can be pooled to conduct meta-analysis and so contribute to generalizable and replicable research findings. CREP is careful to not interpret any single result. CREP has recently joined forces with the psychological science accelerator (PsySciAcc), a globally distributed network of psychological laboratories accelerating the accumulation of reliable and generalizable results in the behavioral sciences. The Department of Psychology at UiT is part of the network and has two ongoing CREP studies, maintaining open science practices early on. In this talk, we will present our experiences of conducting transparent replicable research, and experience with preprints from a supervisor and researcher perspective.